The Prevalence and Risk Factors of Postpartum Depression in Western India: A Cross-Sectional Study - Dharti J. Kansagra; Chikitsa D. Amin; Rajendra B. Chauhan (Indian Journal of Community Medicine)
Background: Postpartum depression (PPD) is a nonpsychotic mental health condition associated with child birth. It poses a major global public health challenge as it remains unrecognized most of the time and impairs both the immediate and long-term health of both the mother and child. The study was conducted to estimate the prevalence and associated risk factors for PPD. Materials and Methods: A cross-sectional study was conducted among 450 women who delivered babies within the past 1–12 months and attending a tertiary care hospital during April to November 2021. Systemic random sampling was used to obtain the desired sample size. Basic sociodemographic variables (age, duration of postpartum period, residence, religion, education, occupation, birth spacing, complication during pregnancy, desired gender of child, birth weight of baby) related to pregnancy were collected. The Edinburgh Postnatal Depression Scale was used to estimate the prevalence of PPD. Results: The prevalence of PPD in the study was 14.2%. The mean ± standard deviation age of women was 27.1 ± 4.7 years. Sociodemographic factors such as maternal age, low level of education, and family type and obstetric factors such as age at first pregnancy, parity, and history of abortion were significantly associated with PPD (P < 0.05). Conclusion: Risk factors related to sociodemographic and obstetric history were found to be significantly associated with PPD. To prevent major depression in postpartum, early detection and timely referral are needed.